2020
DOI: 10.3389/fnhum.2020.580813
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Properties of a Brain Network During Spatial Working Memory Tasks in College Students With ADHD Traits

Abstract: This study investigated deficits of spatial working memory in college students with attention-deficit/hyperactivity disorder (ADHD) traits using event-related potentials (ERPs) and the spatial 2-back task. We also computed sensory-level activity using EEG data and investigated theta and alpha neural oscillations, phase-locking values (PLV), and brain networks. Based on the scores from the Adult ADHD Self-Report Scale (ASRS) and Conners’ Adult ADHD Rating Scales (CAARS), an ADHD-trait group ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 93 publications
2
25
2
1
Order By: Relevance
“…To reveal mechanistic background of scale-free coupled dynamics, further clinical trials and animal models are needed using anesthetics, antipsychotics, antiparkinsonian and other medications ( Nasrallah et al, 2017 ). On a final note, a promising field where such visual pattern recognition task could be advantageous is in attention deficit hyperactivity disorder (ADHD) research, where brain network alterations during spatial working memory tasks have already been revealed ( Jang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…To reveal mechanistic background of scale-free coupled dynamics, further clinical trials and animal models are needed using anesthetics, antipsychotics, antiparkinsonian and other medications ( Nasrallah et al, 2017 ). On a final note, a promising field where such visual pattern recognition task could be advantageous is in attention deficit hyperactivity disorder (ADHD) research, where brain network alterations during spatial working memory tasks have already been revealed ( Jang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amplitude scalp maps in Figure 4 also reflected parietal asymmetry at the N2 ERP, in line with prior findings on N2 ( Gruendler et al, 2011 ). Indeed right-biased cortical asymmetry in ADHD has been a common finding, for example in θ band among adults ( Hale et al, 2014 ; Jang et al, 2020 ). Hale et al (2014) suggested that “atypical rightward asymmetry should be broadly reflective of any form of nonoptimized task-directed brain functioning,” which we elaborate on below.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetry was also reflected in the amplitude scalp maps in Figure 3, and indeed right-biased cortical asymmmetry in ADHD has been a common finding, for example in theta band among adults (73, 74). Hale et al (73) suggested that “atypical rightward asymmetry should be broadly reflective of any form of non-optimized task-directed brain functioning”, which we elaborate on below.…”
Section: Discussionmentioning
confidence: 63%
“…Jang et al (74) observed somewhat similar results, with weaker theta and stronger alpha for adults with ADHD traits (self-report only: not clinically screened), performing a spatial 2-back task. They also analysed PLV and found Controls had more significant connections in theta band in the first half of their trials.…”
Section: Discussionmentioning
confidence: 75%